Prevalensi Kista Ovarium Di RS Swasta di Jakarta Barat pada tahun 2017-2021 - Lauw, Jessica Amelia; Christina, Shintia; Pasaribu, Donna Mesina (Jurnal MedScientiae, 2024)
Ovarian cysts are generally divided into functional cysts, endometriosis, and neoplasm cysts with benign, borderline and malignant properties. Ovarian cysts occur in 82% of women of productive age. In general, ovarian cysts found are benign and the rest are a journey to malignancy. Detailed prevalence rates regarding ovarian cysts for each type of ovarian cyst have not been found in Indonesia, especially at Hermina Daan Mogot Hospital This type of research is descriptive, using a cross sectional design. This research was carried out at Hermina Daan Mogot Hospital from 2017 – 2021.From the results obtained, the most histopathological diagnosis was endometriosis with a total of 117 subjects (45.5%). The largest age group is 36.7 – 45.6 years old with 96 subjects and the least age category is ≥ 65.7 years old with 8 subjects. The most common type of ovarian cyst is endometriosis. The highest age range is 36.7 – 45.6 years.